Upaya Mengatasi Seks Bebas Pada Remaja Berdasarkan Perspektif 1 Korintus 15:33 - Ronaldo Divalo Ginting; Piter Imanson Damanik; Elieser R Marampa; Kristian Sukatman (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Free sex in teenagers is a phenomenon that is increasingly prevalent. This study aims to explain effective ways to overcome teenage promiscuous sexual behavior, using the view of 1 Corinthians 15:33 in the Bible. Through a qualitative approach, this study analyzed data from in-depth interviews with teenagers and parents as well as a review of related literature. The results show that an approach that emphasizes the development of moral values, open communication between parents and children, as well as the establishment of a supportive environment and promoting healthy lifestyles are key in efforts to reduce promiscuous sexual behavior among adolescents. The implication of these findings is the need to be selective in choosing friends, building a close relationship with God, and conducting continuous character building.